Why the lungs became a target organ due to ischemic-reperfusion syndrome of the limb, caused by the use of haemostatic tourniquet - Volotovska, Nataliya (Journal of Education, Health and Sport, 2020)
Much attention has been paid to the ambiguous effects of the tourniquets and hemostatic bandages - namely the local and systemic consequences of planned operations, as well as the changes that occur after the cessation of bleeding from a wounded limb on the battlefield. However, there is still no consensus on the ischemic-reperfusion syndrome (IRS). Aim. Detect changes in the activity of lipid peroxidation in lung tissue on the background of experimental modifications of IRS. For this goal 260 male white rats aged 5-5.5 months were divided into 5 experimental groups: 1) EG1 - imposition of the tourniquet on the thigh for 2 h; 2) EG2 - modeling of venous blood loss in the amount of 40% of the volume of circulating blood; 3) EG3 - a combination of hemostatic tourniquet and blood loss 4) EG4 - mechanical injury to the thigh bone 5) a combination of hemostatic tourniquet and mechanical trauma. The biochemical study in 10 % lung homogenate was performed by reacting of peroxidation derivatives with thiobarbituric acid. Conclusions. It was found that each of these types of intervention caused the activation of lipid peroxidation in the lungs. The peculiarities of the reaction were such increase of this rate, which was the highest on the background of blood loss combined with the use of a tourniquet. However, the concentration of malonic dialdehyde was higher in the group where the imposition of the tourniquet was combined with mechanical trauma, compared with isolated mechanical trauma of the thigh. This has shown the role of the tourniquet as a factor that complicated the course of traumatic disease due to ischemic reperfusion.